Thermal Efficiency of Solar Steam Generation Approaching 100 % through Capillary Water Transport. (7th November 2019) - Liang, Hanxue; Liao, Qihua; Chen, Nan; Liang, Yuan; Lv, Guiqin; Zhang, Panpan; Lu, Bing; Qu, Liangti
Abstract: Solar‐driven interfacial water evaporation yield is severely limited by the low efficiency of solar thermal energy. Herein, the injection control technique (ICT) achieves a capillary water state in rGO foam and effectively adjusts the water motion mode therein. Forming an appropriate amount of capillary water in the 3D graphene foam can greatly increase the vapor escape channel, by ensuring that the micrometer‐sized pore channels do not become completely blocked by water and by exposing as much evaporation area as possible while preventing solar heat from being used to heat excess water. The rate of solar steam generation can reach up to 2.40 kg m −2  h −1 under solar illumination of 1 kW m −2, among the best values reported. In addition, solar thermal efficiency approaching 100 % is achieved. This work enhances solar water‐evaporation performance and promotes the application of solar‐driven evaporation systems made of carbon‐based materials. Abstract : Eine Injektionskontrolltechnik ermöglicht die Erzeugung eines wasserähnlichen Kapillarzustandes in einem Solarabsorber‐Schaum aus reduziertem Graphenoxid (rGO), der zu einer leistungsstarken solaren Dampferzeugung führt. Die Wasserproduktionsrate erreichte 2.40 kg m −2  h −1 .